2019
DOI: 10.1088/1475-7516/2019/12/051
|View full text |Cite|
|
Sign up to set email alerts
|

Multiscatter capture of superheavy dark matter by Pop III stars

Abstract: If captured by the gravitational field of stars or other compact objects, dark matter can self-annihilate and produce a potentially detectable particle flux. In the case of superheavy dark matter (m X 10 8 GeV ), a large number of scattering events with nuclei inside stars are necessary to slow down the dark matter particles below the escape velocity of the stars, at which point the Dark Matter (DM) particle becomes trapped, or captured. Using the recently developed analytical formalism for multiscatter captur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…In the regime where m X m and v esc v we can calculate C tot analytically, both for multi-scatter (τ 1) and single scatter (τ 1) capture. For details of this calculation see [11]. The main result is that we find a closed form for the following sum:…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…In the regime where m X m and v esc v we can calculate C tot analytically, both for multi-scatter (τ 1) and single scatter (τ 1) capture. For details of this calculation see [11]. The main result is that we find a closed form for the following sum:…”
Section: Resultsmentioning
confidence: 85%
“…22 of BDM17. Two of the authors of this comment have used the formalism of BDM17 to show that dark matter capture can impose an upper limit on the masses of the first stars in [11], hereafter known as IZ19. While working to explore the observable implications of IZ19 (see [12]), the authors of this comment identified another typo and several errors in BDM17.…”
Section: Introductionmentioning
confidence: 99%
“…The multiscatter formalism for a single-component astrophysical object (SCMS) was developed in [36,38] and has subsequently been used to calculate the effects of Dark Matter capture on various astrophysical bodies, including neutron stars, white dwarfs, Pop III stars, and exoplanets [36,38,42,[66][67][68][69]. In this paper, we present a method for calculating the DM capture rate in objects composed of more than one element, then apply this formalism to Pop III stars.…”
Section: Two-component Multiscattering Formalismmentioning
confidence: 99%
“…Based on the potentially observable effects due to captured Dark Matter, several classes of objects have been investigated as useful probes of DM. Below we include a non-exhaustive list of the more recent papers where such effects have been analysed for: Pop III stars [40][41][42][43][44], Neutron Stars [36,39,[45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62], White Dwarfs [36,37,[63][64][65], and exoplanets [66]. The capture mechanism in most of those papers is commonly assumed to be via collisions with one unique nucleus, or, in the case of neutron stars, with neutrons.…”
mentioning
confidence: 99%
“…Then, it is important to estimate the CR value by massive bodies as much as possible. CR for different kind of round massive bodies like the Moon 28,33 , planets (like Earth and exoplanets), 25,[34][35][36] the Sun, 23,37,38 other stars, 6,7,[39][40][41][42][43] compact stars 12,13,44,45 are estimated in the litterature.…”
Section: Introductionmentioning
confidence: 99%